A 3D FRACTURE ENERGY-BASED SMEARED CRACK APPROACH FOR THE NONLINEAR BEHAVIOR OF REINFORCED CONCRETE STRUCTURES - Mourlas, Christos; Markou, George; Papadrakakis, Manolis (My University, 2023)
This research study presents a novel energy-based constitutive model of concrete in the framework of the smeared crack approach. The proposed model constitutes an extension to a previous numerical model [1,2] with an addition of a fracture energy-based algorithmic approach developed by [3]. The uncracked behavior of concrete is based on the experimental evidence of the triaxial behavior of concrete described in the literature [4]. The cracked behavior of concrete is modelled with a fracturing approach while cracking is treated with the smeared crack approach. The proposed modelling approach manages to capture the behavior of reinforced concrete (RC) structures with computational efficiency and numerical accuracy as it combines the experimental triaxial behavior of concrete in an algorithmic framework that can alleviate numerical issues of nonlinear concrete behavior such as cracking. The numerical simulation is implemented by using hexahedral isoparametric finite elements for discretizing the concrete domain and truss elements for the steel reinforcement. The proposed approach has been tested on two RC specimens focusing on structural members with insufficient shear reinforcement and high shear stresses. The numerical behavior has been validated by the comparison of the numerical with experimental data found in the international literature. The effect of choosing different approaches of the smeared crack method (fixed and rotated) is also investigated.
Keywords: Cracking; Fracture, smeared crack approac; 3D FEM; Detailed modeling; Shear behavior